The lin-4 Gene Controls Fat Accumulation and Longevity in Caenorhabditis elegans - Zhu, Chun (Molecular Diversity Preservation International (MDPI), 2010)
Previous studies have determined that lin-4, which was the first miRNA to be discovered, controls the timing of cell fate determination and life span in Caenorhabditis elegans. However, the mechanism of lin-4 involvement in these processes remains poorly understood. Fat storage is an essential aspect of the life cycle of organisms, and the function of lin-4 in fat accumulation is not clear. In this study, we showed that the fat content is reduced remarkably in C. elegans lin-4 mutants. Quantitative RT-PCR analysis revealed a considerable decrease in the levels of SBP-1 and OGA-1 mRNA in lin-4 mutants. We also showed that lin-4 mutants have a significantly shorter life span than wild-type worms. DCF assay experiments showed that the reactive oxygen species (ROS) levels increased and mitochondrial DNA (mtDNA) copy number decreased in loss-of-function lin-4 mutants. These mutants also showed attenuation of locomotion. Taken together, our findings suggest that lin-4 may play an important role in regulating fat accumulation and locomotion and that lin-4 may control the life span of C. elegans by mediating ROS production.